The Use of Response Surface Methodology in Ammonia Oxidation Reaction Study - Marek Inger; Agnieszka Dobrzyńska-Inger; Jakub Rajewski; Marcin Wilk (Journal of Chemistry)
The design of experiments (DoEs) with response surface methodology (RSM) were used to investigate the effect of operating parameters on the ammonia oxidation process. In this paper, the influence of reactor’s load and temperature of reaction as independent variables was investigated. The efficiency of NH3 oxidation to NO and N2O concentration in nitrous gases gas was identified as response variables. As a result of these studies, statistically significant models for two responses variables were developed.